2016
DOI: 10.1002/14651858.cd007491.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Admission avoidance hospital at home

Abstract: Background Admission avoidance hospital at home provides active treatment by healthcare professionals in the patient's home for a condition that otherwise would require acute hospital inpatient care, and always for a limited time period. This is the third update of the original review. Objectives To determine the effectiveness and cost of managing patients with admission avoidance hospital at home compared with inpatient hospital care. Search methods We searched the Cochrane Central Register of Controlled Tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
359
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(376 citation statements)
references
References 45 publications
11
359
0
6
Order By: Relevance
“…6 Hospital in the home services have been defined as those that provide 'an alternative to admission to a hospital or an opportunity for earlier relocation to the home than would otherwise be possible.' 8 An important distinction to make between HiTH services is between those that completely substitute the inpatient stay (admission-avoidance HiTH) 9 and those that facilitate a reduction in the inpatient LOS (early-discharge HiTH). Rather, HiTH services deliver a range of interventions (intravenous antibiotics, antivirals, antifungals, fluids, blood products, inotropes, steroids, and enzyme replacement agents), to a range of patient cohorts (neonatal, paediatric, adult and elderly), requiring treatment for a range of conditions (community-acquired acute infections; hospital-acquired, multi-resistant and complicated infections; acute venous thromboembolism; perioperative anticoagulation; chemotherapy and other cancer care; heart failure management, wound management and mental health care).…”
Section: Introductionmentioning
confidence: 99%
“…6 Hospital in the home services have been defined as those that provide 'an alternative to admission to a hospital or an opportunity for earlier relocation to the home than would otherwise be possible.' 8 An important distinction to make between HiTH services is between those that completely substitute the inpatient stay (admission-avoidance HiTH) 9 and those that facilitate a reduction in the inpatient LOS (early-discharge HiTH). Rather, HiTH services deliver a range of interventions (intravenous antibiotics, antivirals, antifungals, fluids, blood products, inotropes, steroids, and enzyme replacement agents), to a range of patient cohorts (neonatal, paediatric, adult and elderly), requiring treatment for a range of conditions (community-acquired acute infections; hospital-acquired, multi-resistant and complicated infections; acute venous thromboembolism; perioperative anticoagulation; chemotherapy and other cancer care; heart failure management, wound management and mental health care).…”
Section: Introductionmentioning
confidence: 99%
“…Hay que resaltar que el HAD ha sido una de las innovaciones más estudiadas en el marco de la atención sanitaria: en la última actualización de la revisión Cochrane sobre los modelos de evitación de ingresos, son 16 los ensayos clínicos aleatorizados (ECA) analizados (2).…”
Section: Algunos Resultadosunclassified
“…But, the most recent Cochrane review [723] concludes that Home Hospitalization/Early Discharge is indicated for selected groups of elderly patients adding a degree of imprecision to the results for the main outcomes. Moreover, efficient care coordination after Home Hospitalization/Early Discharge is relevant, but it is often an unmet need.…”
Section: Discussionmentioning
confidence: 99%
“…It is of note, however, that recent reports [23456] seem to overcome those limitations by demonstrating maturity and health value generation of Home Hospitalization/Early Discharge. Likewise, the 2016 Cochrane review [7] concludes that Home Hospitalization may constitute an effective alternative to inpatient care for a selected group of elderly patients requiring hospital admission.…”
Section: Introductionmentioning
confidence: 99%